2014
DOI: 10.2174/1389203715666140221120219
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Proteomics: A New Tool for Quality and Safety in Fishery Products

Abstract: Abstract:In order to cope with the increasing demand for fishery products, sensitive technological tools are required to ensure high quality and wholesomeness and to monitor their production process in a sustainable manner while complying with the strict standards imposed by regulatory authorities. Proteomics may assist the industry as it allows an unbiased approach in the discovery of biomarkers that could be used to increase our understanding of different biological, physiological and ecological aspects that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…BUP approaches are now well established in aquatic sciences, as evidenced by the growing number of recent projects of full RNA and DNA sequencing, thus, enabling the access to new genomic information from a considerable number of aquatic species, including fish, crustaceans, bivalve mollusks and lower-order animals, aquatic model organisms, and farmed species. BUP has been particularly relevant to the discovery of novel biomarkers for environmental monitoring and quality control of fish food [62,63]; identification of new biomarkers in sentinel organisms (clams) exposed to inorganic environmental stressors such as copper, arsenic, cadmium and pharmaceuticals [25,64,65]; investigation of the molecular pathogenesis of virus-associated shrimp and fish diseases [66] and susceptibility of two oyster species to a protozoan infection [67]; identification of novel allergens [68]; and characterization of the potential allergenicity of transgenic and non-transgenic fish [69]. Proteomics also succeeded in retrieving protein and peptide markers for authentication of aquaculture products, especially fish and crustaceans [70,71,72].…”
Section: Top-down Proteomics In Aquatic Sciencesmentioning
confidence: 99%
“…BUP approaches are now well established in aquatic sciences, as evidenced by the growing number of recent projects of full RNA and DNA sequencing, thus, enabling the access to new genomic information from a considerable number of aquatic species, including fish, crustaceans, bivalve mollusks and lower-order animals, aquatic model organisms, and farmed species. BUP has been particularly relevant to the discovery of novel biomarkers for environmental monitoring and quality control of fish food [62,63]; identification of new biomarkers in sentinel organisms (clams) exposed to inorganic environmental stressors such as copper, arsenic, cadmium and pharmaceuticals [25,64,65]; investigation of the molecular pathogenesis of virus-associated shrimp and fish diseases [66] and susceptibility of two oyster species to a protozoan infection [67]; identification of novel allergens [68]; and characterization of the potential allergenicity of transgenic and non-transgenic fish [69]. Proteomics also succeeded in retrieving protein and peptide markers for authentication of aquaculture products, especially fish and crustaceans [70,71,72].…”
Section: Top-down Proteomics In Aquatic Sciencesmentioning
confidence: 99%
“…Qualitative and quantitative analyses of food allergens are based on the identification of peptides representative of allergens and considered as allergen markers (signatures) [ 122 , 123 , 124 ]. Peptides are usually released by trypsin (EC 3.4.21.4), an enzyme that is widely used in proteomics [ 122 , 123 , 124 , 125 ]. Recent experiments conducted with the use of mass spectrometry were described by Pilolli et al [ 126 ], Gomaa and Boye [ 127 ] and by Posada-Ayala et al [ 128 ].…”
Section: Peptides Relevant As Allergen Markersmentioning
confidence: 99%
“…Mass spectrometry is a popular identification tool. The significance of mass spectrometry in research into proteins and their fragments was emphasized and extensively discussed in several reviews [ 7 , 19 , 122 , 123 , 124 , 125 , 137 , 138 , 139 , 140 ]. Almost all peptide sequences listed in databases and discussed in bioinformatics studies, including in this review article, were identified by mass spectrometry.…”
Section: Mass Spectrometry As a Tool For Experimental Identificatimentioning
confidence: 99%
“…Peptides belong to a group of compounds that provide information about the composition of food ingredients and food products (6)(7)(8)(9). The analyzed peptides are fragments of allergenic proteins or proteins originating from organisms that are known sources of allergens (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…On-line liquid chromatography with mass spectrometry is an eff ective and popular tool for analyses of allergenic proteins. Trypsin (EC 3.4.21.4), an enzyme frequently used in protein hydrolysis (3,(8)(9)(10), and pepsin (EC 3.4.23.1), a proteolytic enzyme commonly used in studies of allergenicity (10), are used to identify proteins (11).…”
Section: Introductionmentioning
confidence: 99%